Manganese-Enhanced MRI Visualizes V1 in the Non-Human Primate Visual Cortex - Bock, Nicholas A. (2009)
We investigated with MRI at 7 Tesla the accumulation of manganese in the occipital cortex of common marmoset monkeys (Callithrix jacchus) following four fractionated injections of 30 mg/kg MnCl(2)·4H(2)O in the tail vein. We found statistically significant decreases in T(1) in the primary (V1) and secondary (V2) areas of the visual cortex caused by an accumulation of manganese. The larger T(1) shortening in V1 (ΔT(1)=641 ms) relative to V2 (ΔT(1)=491 ms) allowed us to robustly detect the V1/V2 border in vivo using heavily T(1)-weighted MRI. As well, the dorsomedial (DM) and middle temporal (MT) areas of the visual pathway could be identified by their T(1)-weighted enhancement. We showed by comparison to histological sections stained for cytochrome oxidase (CO) activity that the extent of V1 is accurately identified throughout the visual cortex by manganese-enhanced MRI (MEMRI). This represents a means of visualizing functional cortical regions in vivo and could be used in longitudinal studies of phenomena such as cortical plasticity, and for localizing cortical areas non-destructively to guide functional techniques.